OPTIMIZATION, DEVELOPMENT AND EVALUATION OF REPAGLINIDE CONTROLLED RELEASE GASTRO-RETENTIVE FLOATING TABLET USING CENTRAL COMPOSITE DESIGN - PATEL, MAHENDRA; KHAN, MASHEER AHMED (International Journal of Applied Pharmaceutics, 2023)
Objective: The recent study's objective was to optimize and formulate a controlled-release gastro-retentive floating tablet of RG using a central composite design, which provides continuous release of Repaglinide for up to 24 h. Methods: Repaglinide gastro-retentive floating tablet (RG-GRF Tablet) was prepared by direct compression method. The optimization was carried out using a three-factor and three-level Central Composite design. The amount of Eudragit RSPO (A), HPMC K-100M (B) and Sodium bicarbonate (C) were selected as independent variables and the Cumulative % drug release in 1.5 h (DR1.5), Cumulative % drug release in 8 h (DR8), Cumulative % drug release in 24 h (DR24) and Floating lag time (FLT) were used as dependent variables. Results: CCD analysis results shows that predicted and experimental values for optimized formulation were found to be almost similar. Optimized amounts of Eudragit RSPO, HPMC K-100M, and NaHCO3 were 14.351 mg, 44.438 mg, and 10 mg, respectively, with the highest possible desirability value of 0.898. The experimental values at optimized preparation conditions were found to be DR1.5 is 30.68%, DR8 is 64.90%, DR24 is 96.54%, and FLT is 4.41 min. The release data from the optimized formulation were closely matched with the Korsmeyer-Peppas model and in vitro drug release studies indicated that the RG-GRF Tablet continuously releases the drug for 24 h in a controlled manner. Conclusion: Current research concludes that RG-GRF Tablets provide drug release for up to 24 h, and the derived central composite design can be used for forecasting the DR1.5, DR8 and DR24 as well. RG can also be made more bioavailable by extending the gastric residence time.